High-affinity autoantibodies specifically eliminate granulocyte-macrophage colony-stimulating factor activity in the lungs of patients with idiopathic pulmonary alveolar proteinosis - Uchida, Kanji; Nakata, Koh; Trapnell, Bruce C.; Terakawa, Takahiro; Hamano, Emi; Mikami, Ayako; Matsushita, Ikumi; Seymour, John F.; Oh-eda, Masayoshi; Ishige, Ikuo; Eishi, Yoshinobu; Kitamura, Takayuki; et al. (Blood, 2004)
Deficiency of granulocyte-macrophage colony-stimulating factor (GM-CSF) in mice results in pulmonary alveolar proteinosis (PAP) from impaired surfactant catabolism by alveolar macrophages (AMs). Recently, we have shown that neutralizing anti-GM-CSF autoantibodies develop specifically in patients with idiopathic pulmonary alveolar proteinosis (iPAP). Analogous to murine PAP models, it is plausible that the autoantibodies reduce GM-CSF activity, resulting in AM dysfunction and surfactant accumulation. To examine this hypothesis, we estimated the neutralizing activity of the autoantibodies in the lungs of patients and characterized their biologic properties. GM-CSF bioactivity was completely abrogated in the bronchoalveolar lavage fluid (BALF) of patients with iPAP but not in healthy subjects. Autoantibodies were present in the alveoli in high concentrations and colocalized with GM-CSF. They recognized human GM-CSF with high avidity (KAV = 20.0 ± 7.5 pM) and high specificity, reacting with its superstructure and neutralizing GM-CSF activity to a level 4000 to 58 000 times the levels of GM-CSF normally present in the lung. Although target epitopes varied among patients, GM-CSF amino acids 78 to 94 were consistently recognized. Thus, autoantibodies bind GM-CSF with high specificity and high affinity, exist abundantly in the lung, and effectively block GM-CSF binding to its receptor, inhibiting AM differentiation and function. Our data strengthen the evidence associating anti-GM-CSF autoantibodies with the pathogenesis of this disease. (Blood. 2004;103:1089-1098)